2013
DOI: 10.1002/jhet.1105
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Promoted One-Pot Synthesis of Some NovelN-Aryl Isoquinoline Derivatives

Abstract: Homophthalic anhydride 1 reacts with different aromatic amines to produce N‐substituted homophthalimides 2 under microwave irradiation. A rapid microwave‐assisted chemical synthesis of condensed 4‐substituted furo[2,3‐c]isoquinoline‐1,5(2H,4H)‐diones 3 and 5‐substituted‐2,3‐dihydro‐1H‐pyrano[2,3‐c]isoquinoline‐1,6(5H)‐diones 4 involving the condensation of a variety of alkanoyl chlorides with 2‐arylisoquinoline‐1,3‐diones 2 in the presence of base and aprotic solvent is described for the first time. By contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The synthesized compounds exhibited characteristic IR (KBr, ν cm For the in vitro screening pure strains were obtained from Post Graduate Department of Microbiology, Orissa University of Agricultural Technology, Bhubaneswar, India. The organisms were identified [7] and screened using disc diffusion method [11][12]. The compounds were dissolved in dimethyl formamide (6%), which was previously tested for antibacterial activity against all test bacteria and found to have no antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesized compounds exhibited characteristic IR (KBr, ν cm For the in vitro screening pure strains were obtained from Post Graduate Department of Microbiology, Orissa University of Agricultural Technology, Bhubaneswar, India. The organisms were identified [7] and screened using disc diffusion method [11][12]. The compounds were dissolved in dimethyl formamide (6%), which was previously tested for antibacterial activity against all test bacteria and found to have no antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of compound 1 and 2a-e were done as per the reported method [7][8] with little modification. (1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 (B) A novel high-yielding one-pot microwave-assisted synthesis of condensed 5-substituted pyranoisoquinoline-1,6-diones 9 from 2-substituted isoquinoline-1,3-diones 8 and 3-chloropropionyl chloride (1) was reported. 3 (C) Aouf et al reported the titanium tetrachloride mediated addition of 3-chloropropionyl chloride (1) to 2,3,6,7-tetramethyl-1,8-bis(trimethylsilyl)-octa-2,6-diene (10) leading to cyclopentanol derivative 11, which contains three quaternary carbons. 4 Cl Cl …”
Section: Preparationmentioning
confidence: 99%